THE PROBLEM OF DEVELOPMENT ULTRALIGHT COMPOSITE DESIGNS - and and (Municipal economy of cities. Series: «Economy science», 2013)
The article describes features of designing and manufacturing of ultralight composite steel and concrete structures. The results are presented of experimental and theoretical investigations of the combination of lightweight concrete with lightweight steel thin-walled structures.